Analisis Self-Regulated Learning Siswa Delegasi Lomba Multidisiplin dalam Mempertahankan Stabilitas Prestasi Matematika - Galeh Febrian Agustino; Reihana Dwi Avianti; Ahmad Naufal Abhar Fannani; Chil Yatun Nisa (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2026)
Continuous learning and cognitive focus in regular classrooms are challenged when students receive long-term dispensations for external competitions. This study aimed to describe the self-regulated learning profile of student delegates and analyze their cognitive defense strategies for maintaining stable mathematics achievement in regular classes. Using a descriptive qualitative method with a focused case study approach, the research was conducted at SMA Negeri 1 Gebog Kudus. Five National Science Olympiad (OSN) delegates with mathematics grades above the minimum mastery criterion were selected through purposive sampling. Data were collected using a 25-item structured questionnaire and 11 semi-structured interview questions, then analyzed using the Miles, Huberman, and Saldaña model. The findings showed that students’ self-regulated learning was in the very high category. Stability was supported by specific cognitive goal setting, self-instruction to overcome ego-related barriers in help-seeking, and an internal locus of control during self-reflection. A strong internal moral commitment that rejected academic excuses was the most critical factor. The study recommends cooperative learning and peer tutoring to support help-seeking without ego barriers, alongside school-based time management guidance. Future research should involve more varied school settings.